Saberes ambientais: diálogos e construção de uma proposta de ensino para a educação em ciências - NONATO, Kelly Maria de Oliveira (Universidade Federal do Pará, 2020)
Science teaching for the new times requires more dynamic and political approaches, in which the subject of learning can be brought to continuous reflection human action towards society, nature, science and technology. Before this, arose in me concerns about teaching environmental processes. For the porpoise of researching such process, I aimed to analyze the student´s environmental knowledge, in the final years of elementary school (ninth grade), for judging this cycle as the basis of science education. I present the following question as the research problem:” What are the environmental perceptions or knowledge of the students and how do they conceive nature from such knowledge?” In this way, I seek to highlight the processes of teaching and learning through the transversal theme of environment. In this sense, the consolidation of the research took place through a teaching sequence using different methods, such as poetry, music, cinema and theater, favoring the scientific curricular knowledge process. For such activities, I referenced myself in the qualitative research, in the action research mode, since it favors the construction and emancipation of conscious subjects. In order to analyze the empirical material that emerged, I used narrative research that seeks new meanings forthcoming from the research process voices. To that end, I focused on discursive textual analysis in an attempt to capture new understandings of subject´s voices in light of theoretical references. Thus, two axis of analysis emerged entitled: Environmental knowledge, a real effective awareness: understandings and lived senses; and Environmental knowledge and the construction of consciousness: new experiences and new possibilities. In this last axis, there were unfoldment that allowed the emergence of subcategories of analysis, such as: understandings that relate environmental knowledge to urban improvement and environmental awareness: Awakening to its complexity. By diminishing the corpus of research, it was possible to observe that the mediation process is closely linked to communication, to socializing. In this way, the re-signification of the environmental knowledge, and the reflection on them, are new apprenticeship that take place in the most diverse forms of mediation that long for dialogue, recognizing that the construction of consciousness occurs in the experience with another, first, and thus, enables the formation of subjectivity.